Concepts, challenges and market potential for online food retailing in Germany - Werner Delfmann; Sascha Albers; Ralph Müßig; Felix Becker; Finn K. Harung; Hannah Schöneseiffen; Vitaly Skirnevskiy; Mirko Warschun; Jens Rühle; Philipp Bode; Christian Kukwa; Niklas Vogelpohl (University of Cologne, Department of Business Policy and Logistics, 2011)
Online food retailing is high on the current agendas of European retailers - again. Many companies tried to enter and conquer this market in the beginning of 2000's when e-commerce was seen as revolutionizing not only the retail business, but the way in which business is conducted in general. Many of these pioneers of online food retailing failed and when the e-commerce bubble burst, online food retailing was almost forgotten in many European countries, inter alia, in Germany. However in some countries retailers not only managed to survive, but to provide value to customers and develop a new market. Online grocery sales per capita in the UK, Switzerland and Belgium are exteuro82, exteuro23 and exteuro18 respectively, while they reach only exteuro2 in Germany. This is surprising since no major structural characteristics can be identified to mitigate internet-based retailing in Germany compared, say, to the United Kingdom. The United Kingdom can be clearly considered as the most developed online food retailing market worldwide, with exteuro5.5 billion market sales of online groceries in 2010. In contrast, online grocery sales in Germany are estimated at only exteuro200 million, which is nearly 27 times less than that of its European neighbor (A.T. Kearney Research, 2011). Also in relative terms the UK online grocery market represent around 4.5% of the total grocery market, compared to only 0.2% in Germany. The German market lags behind other European markets in online food retailing, and our analysis hints at a significant growth potential here. In this study that is based on expert interviews with representatives of large retailers and a survey of more than 600 respondents we identify the reasons for customers' hesitant approach to online retailing and identify strategic options for retailers to successfully operate in this promising segment of the retail industry, that will develop rapidly.
Keywords: 650; Lebensmitteleinzelhandel; E-Business; Geschäftsmodell; Konsumentenverhalten; Erfolgsfaktor; Marktpotential; Deutschland